原函数

$$
F’(x)=f(x) \Rightarrow \int f(x)dx=F(x)+C
$$

$$
F’(x)=f(x) \Rightarrow \int_{a}^{b}f(x)dx=F(b)-F(a)
$$

变限积分

$$
G(x)=\int_{a}^{x}f(t)dt \Rightarrow G’(x)=f(x) \Rightarrow \frac{d}{dx}\int_{a}^{x}f(t)dt=f(x) \Rightarrow \int f(x)dx=\int_{a}^{x}f(t)dt+C
$$

洛必达法则

$$
\lim_{x \to a}f(x)=g(x)=0 \Rightarrow \lim_{x \to a} \frac{f(x)}{g(x)}=\lim_{x \to a}\frac{f’(x)}{g’(x)}
$$

$$
\begin{aligned}
\lim_{x \to a} \frac{f(x)}{g(x)}
=\lim_{x \to a} \frac{\frac{f(x)-0}{x-a}}{\frac{g(x)-0}{x-a}}
=\lim_{\Delta x \to 0} \frac{\frac{f(a+\Delta x)-f(a)}{\Delta x}}{\frac{g(a+\Delta x)-g(a)}{\Delta x}}=\frac{f’(a)}{g’(a)} (g’(a) \not= 0)
\end{aligned}
$$

$$
\lim_{x \to a} f(x)=0,g(x)=+\infty \Rightarrow \lim_{x \to a}f(x)=0,\frac{1}{g(x)} = 0 \Rightarrow \lim_{x \to a} f(x)g(x)=\lim_{x \to a}\frac{f(x)}{\frac{1}{g(x)}}
$$

$$
\lim_{x \to 0}f(x)=g(x)=0 \Rightarrow \lim_{x \to 0}f^{g(x)}(x)=\lim_{x \to 0}e^{g(x)\ln f(x)}
$$

收敛性判断

$$
\sum_{i=0}^{\infty}a_i = C \Rightarrow \lim_{i \to \infty} \left|\frac{a_{i+1}}{a_i}\right| < 1
$$